2014
DOI: 10.1016/j.jbiomech.2014.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Promoting increased mechanical properties of tissue engineered neocartilage via the application of hyperosmolarity and 4α-phorbol 12,13-didecanoate (4αPDD)

Abstract: Osteoarthritis, a degenerative disease of the load-bearing joints, greatly reduces quality of life for millions of Americans and places a tremendous cost on the American healthcare system. Due to limitations of current treatments, tissue engineering of articular cartilage may provide a promising therapeutic option to treat cartilage defects. However, cartilage tissue engineering has yet to recapitulate the functional properties of native tissue. During normal joint loading, cartilage tissue experiences variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Increases in chondrogenic marker expression, matrix production, and cell proliferation were not observed in the GFP− (nonchondrogenic) cells after GSK101 stimulus, possibly due to the distinct Ca 2+ signaling response of these cells, or due to this heterogeneous cell population having already differentiated into other cell lineages. The enhanced biosynthesis of GFP+ cells is consistent with previous studies showing that stimulation of TRPV4 with mechanical, osmotic, or chemical activators results in a strong anabolic response in primary chondrocytes, characterized by significant increases in extracellular matrix synthesis and accumulation 22,38,39 . It is important to note that while mechanical factors can enhance chondrogenesis, 40 the ability to accelerate cartilage tissue formation using a small molecule chemical agonist may have significant advantages over the use of growth factors or direct mechanical stimulation (eg, in a bioreactor), particularly for large, inhomogeneous, or anatomically shaped tissue grafts 41,42 …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Increases in chondrogenic marker expression, matrix production, and cell proliferation were not observed in the GFP− (nonchondrogenic) cells after GSK101 stimulus, possibly due to the distinct Ca 2+ signaling response of these cells, or due to this heterogeneous cell population having already differentiated into other cell lineages. The enhanced biosynthesis of GFP+ cells is consistent with previous studies showing that stimulation of TRPV4 with mechanical, osmotic, or chemical activators results in a strong anabolic response in primary chondrocytes, characterized by significant increases in extracellular matrix synthesis and accumulation 22,38,39 . It is important to note that while mechanical factors can enhance chondrogenesis, 40 the ability to accelerate cartilage tissue formation using a small molecule chemical agonist may have significant advantages over the use of growth factors or direct mechanical stimulation (eg, in a bioreactor), particularly for large, inhomogeneous, or anatomically shaped tissue grafts 41,42 …”
Section: Discussionsupporting
confidence: 86%
“…Not only was Trpv4 expression and function associated with chondrogenesis, we also observed that activation of TRPV4 signaling in with mechanical, osmotic, or chemical activators results in a strong anabolic response in primary chondrocytes, characterized by significant increases in extracellular matrix synthesis and accumulation. 22,38,39 It is important to note that while mechanical factors can enhance chondrogenesis, 40 the ability to accelerate cartilage tissue formation using a small molecule chemical agonist may have significant advantages over the use of growth factors or direct mechanical stimulation (eg, in a bioreactor), particularly for large, inhomogeneous, or anatomically shaped tissue grafts. 41,42 The specific mechanisms involved in TRPV4 enhancement of chondrogenesis remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…TRPV4 has previously been shown to be an important mechanosensitive ion channel that mediates the cellular response to compressive stimulation and ultimately affects neotissue functional properties 21 ; without a functioning TRPV4 channel, compressive stimulation did not increase the compressive modulus. In our hands, TRPV4 agonism resulted in up to a 153% increase in tensile properties 36 , 37 . Here we showed that TRPV4 channel function is needed to sense tension stimulation and initiate signal transduction to result in functional property increases (Young's modulus), as GSK205 inhibition of TRPV4 during tension stimulation eliminated the emergent tissue-level response to tension ( Figure 3b ).…”
Section: Tension Stimulation Modes Of Actionmentioning
confidence: 55%
“…Since there is no provided ECM to offer bulk to the construct, a high number of cells is usually required to produce appreciable tissues [ 114 , 116 , 117 ]. Similarly, as there is no ECM to guide the cells, there is often a need for mechanical and chemical stimulation of the cultures in order to guide ECM production [ 116 , 121 , 122 ]. This also means that the start of the culture can be precarious for the cell phenotype as there are no physical signals coming from the ECM.…”
Section: Scaffold-free Culture Systemsmentioning
confidence: 99%